Prevalence of lead poisoning among artisanal gold miners in French Guiana in 2022: a multicenter cross-sectional observational survey - Maylis Douine; Virgile Korsec; Alice Sanna; Lorraine Plessis; Teddy Bardon; Antoine Adenis; Mathieu Nacher; Martha Suarez-Mutis; Stephen Vreden; Olivier Mathieu; Yann Lambert (BMC Public Health)
Abstract Background Lead poisoning is a significant public health issue globally. In French Guiana, a French overseas territory in South America, several studies have reported widespread lead exposure in the local population. However, the associated risk factors remain insufficiently understood. People working in informal gold mining share part of their lifestyle with French Guianese communities. The objectives of this study were to describe the prevalence of lead poisoning and to identify associated risk factors among gold mine workers in 2022. Methods This cross-sectional descriptive study was based on data collected by questionnaire and blood sampling. Persons working in informal gold mines were enrolled on the logistic rear bases on the Surinamese and Brazilian sites of the bordering rivers. Blood lead levels were measured on dry blood spots (50 µl). Using a threshold of 100 µg/L, single and multiple regressions were used to assess the associated factors. Results Among the 526 persons included, the median age was 38 years and 73.5% were men. The prevalence of lead poisoning was 44.7% (95%CI = 40.4%-49.0%). The factors associated with a BLL over 100 µg/L were: amount of time spent in gold mining (OR = 1.31 [1.09–1.58]), occupation with mud exposure (OR = 1.67 [1.13–2.48]), working in the Southwestern region (OR = 2.09 [1.34–3.27]) and consuming game (OR = 1.58 [1.06–2.36]). Conclusion The people working on gold mining sites are highly exposed to lead poisoning. The risk factors are suggestive of environmental contamination and differ from those suspected in the population of French Guiana. Trial registration This study is registered on ClinicalTrials.gov under the identifier NCT05540470 (registered on September 12, 2022).